Employee Engagement and Organizational Commitment as Mediators: The Impact of Green HRM on Employee Performance - Permadi, I Komang Oka; Purnawan, I Kadek; Mirayani, Luh Putri Mas; Sanjiwani, Putu Ari Pertiwi (Universitas Batanghari Jambi, 2025)
This study aims to determine the effect of G-HRM on employee performance by considering the mediating function of employee engagement and organizational commitment. This study used quantitative methods and collected data through a survey among 70 staff members from 10 Fitness Plus outlets in Bali. Structural Equation Modeling (SEM) data analysis was used to determine the relationship between variables and the possible mediating role. The results revealed that, both directly and through higher employee engagement, G-HRM significantly improves employee performance. The relationship between G-HRM and employee performance is largely mediated by employee engagement. In contrast, organizational dedication does not show a significant mediating effect on this relationship. In addition, this study also found that G-HRM can improve employee performance, the effect is most significant if accompanied by increased employee emotional involvement in their work.